A SEISMOACOUSTIC ANALYSIS OF THE GAS-PIPELINE EXPLOSION NEAR GHISLENGHIEN IN BELGIUM - Evers L.G.; Haak H.W.; Ceranna L.; Le Pichon A.; Whitaker R.W. (My University, 2007)
A high-pressure gas pipeline exploded near Ghislenghien in Belgium, on 30 July 2004. Seismic energy of this event was recorded at three nearby seis-mometers. The origin time of the explosion was determined by analyzing the Ray-leigh waves and found to be 06h55m272sec coordinated universal time (UTC). Ground truth of the explosion was invoked to assess the accuracy of the location derived from infrasound data recorded over Western Europe. Different infrasonic phases were identified by using array-processing techniques and raytracing through atmospheric models. The analysis showed that the derived location was situated 13 km from the true location. The total area of the uncertainty ellipse, or area to be searched if the source was of unknown origin, was 690 km 2 . After the origin time and location, the yield was calculated by comparing infrasonic stratospheric ampli-tudes with those from a high-explosives dataset and was estimated at 40.9 tons high-explosives equivalent. In summary, this study illustrates the capability of seismic and infrasound data in forensic investigations. Furthermore, the potential of infra-sound as a monitoring or verification technique is addressed.